استراتيجيات التكيف الإيجابية مع الضغوط النفسية وعلاقتها بالذكاء الانفعالي لدى طلاب الجامعة - شاكر، راندا عماد فتحي; سليمان، سليمان محمد; إبراهيم، أماني سعيدة سيد (جامعة بني سويف - كلية التربية, 2021)
هدف البحث الحالي إلى الكشف عن العلاقة بين استراتيجيات التكيف الإيجابية مع الضغوط النفسية والذكاء الانفعالي، لدى طلاب الجامعة، واعتمد البحث على المنهج الوصفي الارتباطي، وتكونت عينة البحث من (٣٠٢) طالبا وطالبة من كليتي (الآداب، العلوم) بجامعة بني سويف، واستخدمت الباحثة عدد من الأدوات تمثلت في؛ مقياس الذكاء الانفعالي (إعداد الباحثة)، ومقياس استراتيجيات التكيف الإيجابية مع الضغوط النفسية (إعداد الباحثة)، واستعانت الباحثة بالأساليب الإحصائية المستخدمة التالية: (معامل الارتباط، معامل ألفا كرونباخ، اختبار "ت" )، وتوصلت النتائج إلى: وجود علاقه ارتباطية طردية ذات دلالة إحصائية بين استراتيجيات التكيف الإيجابية مع الضغوط النفسية والذكاء الانفعالي لدى طلاب الجامعة، وعدم وجود فروق ذات دلالة إحصائية في الذكاء الانفعالي، لدى طلاب الجامعة، تعزي لمتغير الجنس (ذكور، إناث)، وذلك في البعد (الأول والثاني والثالث والخامس) والمقياس ككل، بينما يوجد فرق دال إحصائيا في الذكاء الانفعالي، لدى طلاب الجامعة، في البعد الرابع لصالح الذكور، ولا توجد فروق ذات دلالة إحصائية في الذكاء الانفعالي، لدى طلاب الجامعة، تعزي لمتغير التخصص (علمي، أدبي)، وعدم وجود فروق ذات دلالة إحصائية في استراتيجيات التكيف الإيجابية مع الضغوط النفسية، لدى طلاب الجامعة، تعزي لمتغير الجنس (ذكور، إناث)، وعدم وجود فروق ذات دلالة إحصائية، في استراتيجيات التكيف الإيجابية مع الضغوط النفسية، لدى طلاب الجامعة، تعزي لمغير التخصص (علمي، أدبي)، وذلك في البعد (الثاني والثالث والرابع والخامس) والمقياس ككل، بينما يوجد فرق دال إحصائيا في استراتيجيات التكيف الإيجابية مع الضغوط النفسية، لدى طلاب الجامعة، وذلك في البعد الأول لصالح التخصص الأدبي.
The aim of the current research is to reveal the relationship between positive coping strategies with psychological stress and emotional intelligence among university students, and the research was based on the relational descriptive approach, and the research sample consisted of (302) students from the faculties of (Arts and Sciences) at Beni Suef University. The researcher used a number of tools, including: Emotional intelligence scale (the researcher's preparation), and the scale of positive coping strategies with psychological stress (the researcher’s preparation). The researcher used the following statistical methods used: (correlation coefficient, Cronbach's alpha coefficient, “T” test).The results concluded: There is a statistically significant positive correlation between emotional intelligence and positive coping strategies with psychological stress among university students, and the absence of statistically significant differences in emotional intelligence among university students attributable to the gender variable (males, females), in the dimension (First, second, third, and fifth) and the scale as a whole, while there is a statistically significant difference in emotional intelligence among university students in the fourth dimension in favor of males, and there are no statistically significant differences in emotional intelligence among university students. Attributing to the variable of specialization (scientific, literary), and the absence of statistically significant differences in positive coping strategies with psychological stress, among university students, attributable to the variable of sex (males, females), and the absence of statistically significant differences in positive coping strategies with psychological stress Among university students, you attribute to the variable of specialization (scientific, literary) in the dimension (second, third, fourth, and fifth) and the scale as a whole, while there is a statistically significant difference in positive coping strategies with psychological stress among university students, in the first dimension in favor of specialization Literary.
Keywords: الاستراتيجيات التعليمية -- التكيف الإيجابية -- الضغوط النفسية -- البرامج الإرشادية -- طلبة الجامعات